Sistema para la evaluación de parámetros eléctricos de micro inversores de sistemas fotovoltaicos - Campos-Rojas, Javier (Instituto Tecnológico de Costa Rica, 2017)
This document presents the development of a system to evaluate electrical parameters in a micro inverter of photovoltaic systems, for which a network emulator was designed programming algorithms in Python for the management of bipolar power supplies, which perform characterization routines in order to determine the behavior in ranges of voltage, frequency and response to harmonic injection in the electric network. An energy quality analysis program was also designed to determine the levels of total harmonic distortion(THD), mismatches and amplitudes during the experimental results of the characterization.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2017.
Keywords: Python; Generación; FFT; Sistemas fotovoltaicos; Micro inversores